Conocimientos y prácticas en salud sexual de los estudiantes de la Universidad de Antioquia, Medellín, Colombia, 2014 (2014)
ABSTRACT: Introduction Sexuality is inherent to humanity; its experience is part of daily life and has effects on sexual health. Sexual education takes place through the several stages of life, including university life. Objective: to determine the level of knowledge and practices in terms of sex¬ual health of undergraduate students at Universidad de Antioquia. Materials and methods A cross-sectional descriptive study was conducted in the 2012-2014 period, in a representative sample of 2126 students from all campus of Universidad de Antioquia; a virtual survey was also applied, including a questionnaire on knowledge of sexual health that was rated at four levels: excellent, good, acceptable, and poor. Results High frequency of risky practices were found: 79.8% did not use or irregularly resorted to the condom, 52.5% did not use a condom at last intercourse, 23.6% claimed sexual relationships with people other than the couple, and 21.8% had more than three couples during the past year; with marked gender difference. In the assessment, acceptable and deficient levels were the most common ones, higher in men, students com¬ing from other regions and students enrolled in social sciences, engineering, and natural sciences academic programs, and adolescent students. Conclusions This study found high frequency of risky practices for sexual health and poor knowledge of the topic. The differences found in risky behavior among men and women are highlighted, as well as in terms of the level of knowledge students have on sexual health; situa¬tions to be considered in the reorientation of sexual education programs.